Pengaruh Perubahan Penggunaan Lahan terhadap Ketercukupan Air Irigasi dan Upaya Pelestarian Air Subdas Bedog di Provinsi Daerah Istimewa Yogyakarta - Y.B. Aprin Sugeng Jatmika; L. Setyawan Purnama; Slamet Suprayogi (Syntax Corporation Indonesia, 2024)
Bedog’s sub-watershed (SubDAS) underwent a change in land use, an increase in water discharge, a scarcity in irrigation, and a need to preserve water resources. The aim of the research is to identify the impact of land use changes on water discharge, evaluate the adequacy of agricultural irrigation water, and evaluate water conservation efforts. This research uses quantitative approach to examine rainfall, river debit, and map of changes in land use through ArcGIS; and qualitative approach to see irrigation sufficiency and water preservation. A rational method is also used to analyse flood discharge and classification of flow regime coefficient to determine sub-watershed quality. Findings in this research includes: an increase in coefficient value of land use by 4.29% as well as in the peak runoff (two-year return period) by 13.75 m3/s – both in the span of 2013-2022 – a high coefficient value of flow regime and a decrease in irrigation discharge, hence the urgency to improve water resources’ mechanical conservation.